CIRCUMSTANTIAL ELEMENTS ANALYSIS OF LYDIA MACHOVA’S SPEECH IN THE SECRETS OF LEARNING A NEW LANGUAGE TED TALKS: A SYSTEMIC FUNCTIONAL LINGUISTICS STUDY - Apriliasih Setiawati; Erni Hastuti; Teddy Oswari (Journal of Language and Literature, 2022)
Systematic Functional Linguistic (SFL) views language as a sign system that can be analysed based on language structure and language use. The researchis about circumstantial elements of Lydia Machova’sspeech at The Secret of Learning a New Language TED Talks. This study aims to find out the types of circumstantial elements and the most dominants circumstantial in Lydia Machova’s utterances. This research used the theory proposed by Halliday & Mattiessen (2004). This research used descriptive quantitative research. The source of data was taken from utterances of Lydia Machova which provides the circumstantial elements. The research resultshown all types of circumstances occurred in Lydia Machova utterances. The highest usages of circumstance are location due to the function of location give the information about the absolute place where the experience, methods and tips occurred and also give the details of time when the moment actually happened for how long and how often.